Indigenous persistence and entitlement: Noongar occupations in central Perth, 1988–1989 and 2012 - Cox, S.; Birdsall-Jones, Christina; Jones, R.; Kerr, T.; Mickler, S. (ACADEMIC PRESS LTD ELSEVIER SCIENCE LTD, 2016)
In 1988–1989 and again in 2012 Noongar Aboriginal groups occupied high profile riverside sites in close proximity to the centre of Perth, Western Australia. On both occasions they were claiming rights to land from which their ancestors had been removed in the early nineteenth century by British colonial settlers. During a relatively brief period of struggle and interaction between the Indigenous and settler groups following the proclamation of the Swan River Colony in 1829, the Noongar population of what is now the Perth Metropolitan Area were effectively dispossessed of their land. Indeed, from the mid nineteenth to the mid twentieth century Aboriginal people were required to obtain written permits in order to enter the urban area of Perth. In spite of this, the local Noongar population has maintained an ongoing physical, emotional and spiritual connection to their traditional country and, in particular, to certain sites within it. Two of these sites, Goonininup/the Old Swan Brewery, in 1988–1989, and Matagarup/Heirisson Island, in 2012, have been occupied by Noongar groups asserting their rights to this land. This paper will describe and compare both sites of occupation with particular reference to the methods and motivations of the occupiers and the attitudes and responses of the wider metropolitan population to these events. It will also place them in the wider context of ongoing debates over the acknowledgement of Aboriginal claims to and rights over sites of Indigenous significance and of land occupations as a form of protest.